Recombinant scorpion toxins: Focus on four-disulfide peptide blockers of Kv1-channels. Issue 1 (1st January 2018) - Nekrasova, Oksana; Yakimov, Sergey; Kirpichnikov, Mikhail; Feofanov, Alexey
ABSTRACT: We have recently developed a simple and effective bioengineering approach to large-scale production of alpha-KTx, peptide toxins from scorpion venoms, that block voltage-gated potassium channels with high affinity and specificity. This approach was successfully approved for different peptides containing three disulfide bonds. To extend this method to production of peptide toxins with four disulfide bridges, in particular, maurotoxin and hetlaxin, appropriate conditions of a cleavage reaction with tobacco etch virus (TEV) protease need to be found. For this, the interplay between efficiency of TEV hydrolysis and sensitivity of the target peptides to disulfide reducing agents was studied, and optimized protocols of TEV cleavage reaction were worked out. Maurotoxin and hetlaxin were produced in a folded form avoiding in vitro renaturation step with yields of 14 and 12 mg/liter of culture, respectively.